ONE’S FACEBOOK STATUS, A REFLECTIVE SELF REPRESENTATION - Dewi Puspitasari (P3M STAIN Kudus, 2016)
The phenomena of using social media in the society increases significantly.  Social media is being the shifting phenomenon within communication, in which people get connected through the number of internet facilities, for the users have grown massively (Shirky 2011:1). A text as shown in the Facebook status expresses the intention and background underlying it. The writer may deny the fact, however, lexicon, markers, and the choice of a visual support in the sentence clearly reflect the hidden message of the text. From the attitude in the stance shows that the writer comes across his idea in a negative tension (attitude).